2016
DOI: 10.1007/s10389-016-0714-y
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy-based opiate substitution treatment and related health services: a study of 508 patients and 111 pharmacies

Abstract: Background and Aims: Community pharmacies have a central role in the provision of Opiate Substitution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…However, PWUD expressed positive comments about pharmacy staffcomparing them favourably to other pharmacies. This reflects previous research in which being treated with a positive attitude was valued (Laird et al 2016).…”
Section: Discussion Of Main Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…However, PWUD expressed positive comments about pharmacy staffcomparing them favourably to other pharmacies. This reflects previous research in which being treated with a positive attitude was valued (Laird et al 2016).…”
Section: Discussion Of Main Findingssupporting
confidence: 85%
“…The approach allowed staff to reflect on their behaviour and identify previous, potentially discriminatory practice. Attitudes compared favourably with previous national (Matheson et al 2016) and local data (Laird et al 2016) and demonstrated that the participating pharmacies were already well disposed to this patient group. Despite this, there were some aspects of their practice that were highlighted by training as being potentially stigmatising.…”
Section: Discussion Of Main Findingsmentioning
confidence: 69%
“…19 , 20 A recent study in Scotland found that provision of health services such as counseling, treatment referral, and management of other common ailments were key factors in patients choosing to receive opioid substitution treatment at the pharmacy. 21 Similar opportunities need to be created for pharmacists in the US to be able to monitor SUD patients and refer when necessary for further evaluation and treatment. This would require both more education and the reduction of time and reimbursement barriers in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“… 56 Privacy was a factor for participants when choosing a particular pharmacy for opioid substitution therapy, 44 favouring those which could offer a private room. 111 For sexual health, teenagers reported feeling embarrassed to discuss birth control medication in the pharmacy. 61 In addition, participants were concerned about the lack of a comfortable space to have intimate partner violence screening consultations, 70 and homosexual men reported the lack of a safe place for sexual health screening.…”
Section: Resultsmentioning
confidence: 99%